Shelf Life of Fresh and Pasteurized Organic Passion Fruit (Passiflora Edulis F. Flavicarpa Deg.) Pulp - Janzantti, Natália S.; Santos, Graciela C.; Monteiro, Magali (Hindawi, 2012)
The shelf life of the organic passion fruit pulp, both fresh and pasteurized at 70C and 90C and stored under refrigeration, was evaluated. The heat treatment did not affect the sensory and physicochemical characteristics of the pasteurized pulps when compared with the fresh pulp, except for the ascorbic acid content. The pulps were also microbiologically safe. The pulps pasteurized at 70 and 90C were suitable for consumption for a minimum shelf-life period of 207 days of storage under refrigeration and for the fresh pulp it was attributed a shelf-life period of 60 to 90 days. The pulp pasteurized at 70C showed higher acceptance scores for all the attributes and purchase intention scores, suggesting a more stable behavior and higher sensory quality. Practical Applications: This work intended to evaluate the influence of the minimum pasteurization on the sensory acceptance and microbiological and physicochemical characteristics of the organic passion fruit pulp stored under refrigeration, with the aim to identify the shelf life. Heat treatment is one of the processes used for food preservation. Lower pasteurization temperature than that used by the Brazilian industries and storage under refrigeration showed to be appropriate for passion fruit pulp quality. In this way, the microbiological, physicochemical and sensory features of passion fruit were preserved. This work can be used as a reference for passion fruit pasteurization, which is able to increase the shelf life of this fruit while preserving its desirable original features. Journal Compilation © 2012 Wiley Periodicals, Inc.